Influence of a probiotic/trace mineral mixture on growth performance and salmonella choleraesuis shedding in nursery pigs - Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We tested a probiotic/trace mineral mixture using a bacterial challenge model in high-health status pigs. We examined the influence of the mixture on growth performance, hematologic parameters, haptoglobin concentration, and Salmonella choleraesuis shedding in nursery pigs. A successful model of S. cholereasuis challenge was established. However, the probiotic/trace mineral mixture did not influence growth performance, bacterial shedding, or other parameters examined in this experiment.
Keywords: Swine; Salmonella choleraesuis; Probiotics; Trace minerals